2020
DOI: 10.1080/03031853.2020.1761845
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the financial efficiency of agricultural cooperatives in South Africa: an application of the Simar–Wilson methodology

Abstract: The SA government has favored cooperatives over other types of corporate entities in its programmes for rural development. This study examines financial efficiency and its determinants for 387 agricultural cooperatives in SA using a two-stage double bootstrap approach. Bias-corrected Data Envelopment Analysis (DEA) efficiency estimates are obtained in the first-stage for the agricultural cooperatives. Next, a Double Bootstrapped Truncated Regression model was estimated to obtain bias-corrected scores. The mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…These aforementioned variables, together with poor managerial aptitude, age, size and governance, were found to be the major influential factors in agricultural cooperative efficiency, the lack of which ultimately results in cooperative failure (Yobe et al, 2020). While a majority of agricultural cooperatives in South Africa are financially inefficient (Yobe et al, 2020), the efficiency of agricultural cooperatives is an important factor, as it determines the profits and dividends for each member and contributes to the members' livelihood. Table 1 below summarises some of the commonly cited reasons for agricultural cooperative failure in South Africa.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…These aforementioned variables, together with poor managerial aptitude, age, size and governance, were found to be the major influential factors in agricultural cooperative efficiency, the lack of which ultimately results in cooperative failure (Yobe et al, 2020). While a majority of agricultural cooperatives in South Africa are financially inefficient (Yobe et al, 2020), the efficiency of agricultural cooperatives is an important factor, as it determines the profits and dividends for each member and contributes to the members' livelihood. Table 1 below summarises some of the commonly cited reasons for agricultural cooperative failure in South Africa.…”
Section: 4mentioning
confidence: 99%
“…The National Planning Commission's National Development Plan places agriculture at the centre of rural economic growth, development and employment creation (NPC, 2011). In this regard, across the globe, agricultural cooperatives have been widely acknowledged as a vehicle to uplift poor people from deep poverty in developing countries, including South Africa (see Ortmann & King, 2007;Mojo et al, 2017;Sebhatu et al, 2020;Yobe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides technology having an important role in financial efficiency, good governance and professional management have also driven financial efficiency. The oldest financial institution like cooperative becomes more efficient than new cooperative (Yobe et al, 2020). A cooperative or financial institution with long experience tends to have good and professional management.…”
Section: Financial Efficiency and Technologymentioning
confidence: 99%
“…Internet used properly also helps to create financial efficiency (Botti et al, 2014). Another research found out financial efficiency also came from good governance and professional treatment of a financial institution (Yobe et al, 2020;Botti, 2014). Even Sufian (2004) revealed that good managerial and governance in financial institutions should produce efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research on the efficiency of agricultural cooperatives in South Africa discovered that some cooperatives were inefficient. The age and size of the cooperative, the gender of the manager, and indicators of how to manage and train it are all factors that influence this inefficiency (Yobe at al., 2020). Farrel (1957) and Coelli (1998) distinguish three types of efficiency: technical efficiency, allocative efficiency, and economic efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%